Sustainable logistics and supply chain management: a holistic view through the lens of the wicked problem. (2018) - Russell, Dawn M.; Swanson, David; Blinge, Magnus
This study takes a holistic perspective of sustainable logistics and supply chain management (SLSCM), exploring the interdependencies among sustainability, financial strength and customer performance in logistics and supply chain management. Firms often struggle to understand when sustainable performance is improving and most importantly, what it costs them in terms of financial and customer performance. The theoretical lens of the wicked problem provides a framework to understand why sustainability performance shows mixed results. Hypotheses that investigate aggregate-level links between sustainable practices of global companies are tested with regression analysis and firm-level data from three widely used databases. Efforts to improve SLSCM can have a positive impact on performance; however, it comes at a price. For example, we find that firms that achieve the highest sustainability recognition have a lower return on assets (ROA) and that a leadership position in sustainability performance requires resources and a long-term view of return on investment.